Association Between Vitamin D Supplementation and Fall Prevention - Wei, Fei-Long; Li, Tian; Gao, Quan-You; Huang, Yuli; Zhou, Cheng-Pei; Wang, Wen; Qian, Ji-Xian (Frontiers in Endocrinology, 2022)
Abstract Background: Falls occur frequently among older individuals, leading to high morbidity and mortality. This study was to assess the efficacy of vitamin D in preventing older individuals from falling. Methods: We searched the PubMed, Cochrane Library, and EMBASE databases systematically using the keywords “vitamin D” and “fall” for randomized controlled trials (RCTs) comparing the effects of vitamin D with or without calcium supplements with those of a placebo or no treatment on fall incidence in adults older than 50 years. A meta-analysis was performed to calculate risk ratios (RRs), absolute risk differences (ARDs) and 95% CIs with random-effects models. Results: A total of 38 RCTs involving 61 350 participants fulfilled the inclusion criteria. Compared with placebo, high-dose vitamin D (≥ 700 IU) can prevent falls (RR, 0.91 [95% CI 0.84 to 0.99]; ARD, -0.06 [95% CI, -0.10 to -0.02]). Low-dose vitamin D (<700 IU) was not significantly associated with falls. Subgroup analysis showed that supplemental calcium, 25(OH) D concentration and frequency influenced the effect of vitamin D in preventing falls. Sensitivity analysis showed that vitamin D prevented falls, which was consistent with the primary analysis. In addition, the active form of vitamin D also prevented falls. Conclusion: In this meta-analysis of RCTs, doses of 700 IU to 2000 IU of supplemental vitamin D per day were associated with a lower risk of falling among ambulatory and institutionalized older adults. However, this conclusion should be cautiously interpreted, given the small differences in outcomes.